Effect of the cooldown type on session rating of perceived exertion - Rodríguez-Marroyo, J. A.; González, B.; Foster, C.; Belén Carballo-Leyenda, A.; Villa, J. G. (International Journal of Sports Physiology and Performance, 2021)
Purpose: This study investigated the effect of cooldown modality (active vs passive) and duration (5, 10, and 15 min) on session rating of perceived exertion (sRPE). Secondarily, the possible influence of training sessions` demand on this effect was studied. Methods: A total of 16 youth male soccer players (15.7 [0.4] y) completed 2 standardized training sessions per week across 6 weeks. During weeks 1 to 2, 3 to 4, and 5 to 6, cooldown lengths of 15, 10, and 5 minutes were studied, respectively. Using a crossover design, players were randomly assigned to 2 groups and each group performed 1 of 2 different cooldown interventions. Passive and active cooldown interventions based on static stretching and running exercises were studied. Heart rate and sRPE were recorded during all training sessions. Results: The lowest sRPE was observed when passive cooldown was performed. When the hardest training sessions were considered, a significant main effect of cooldown modality (P < .01) and duration (P < .05) and an interaction effect between these variables (P < .05) on sRPE were obtained. The lowest (P < .01) sRPE was observed during the longest cooldown (15 min). Conclusion: The findings suggest that sRPE may be sensitive to the selected cooldown modality and duration, especially following the most demanding training sessions.